Corporate Risks and Leadership What Every Executive Should Know about Risks, Ethics, Compliance, and Human Resources. - Mariscotti, Eduardo E. (Productivity Press, 2025)
This book is a wake-up call that allows business leaders to understand the benefits of implementing an effective ethics and compliance program that will help members of organizations make the right decisions and act within the law.
Description based upon print version of record.
Keywords: Industrial management.; Business ethics.; Personnel management -- Moral and ethical aspects.; Corporate culture.; elektronické knihy; electronic books